The Role of Monetary Policy in Stabilizing Inflation: An Islamic Economic Perspective - Istiqomah, Istiqomah; Aviva, Itsla Yunisva (Jurnal Hadratul Madaniyah, 2025)
Monetary policy plays a very important role in stabilizing inflation and maintaining economic balance. In the perspective economics, monetary policy must be based on the principle of justice, prioritize welfare, and avoid usury. This article examines the role of monetary policy in stabilizing inflation from the perspective of Islamic economics. This research uses a descriptive qualitative method with a literature study approarch, where data collection employs secondary data taken from books, journals, and articles that support the theme of this research. Research result indicate that in Islamic economic, stabilizing inflation is achieved through monetary policies that are just and free from usury. However, several sharia economic experts believe that there are some some conventional monetary policy instrumensts that can still be applied, such as reserve requirements, overall and selective credit ceilings, moral suasion, and chages in monetary policy